Global, regional, and national burden of chronic obstructive pulmonary disease from 1990 to 2019 - Wang, Haifeng; Ye, Xiaojuan; Zhang, Yafeng; Ling, Shiliang (Frontiers in Physiology, 2022)
Abstract Background: We aimed to estimate the incidence, mortality, disability-adjusted life years (DALYs) for chronic obstructive pulmonary disease (COPD) in 204 countries and territories. We examined the variations in these trends by country, sex, age group, and sociodemographic index (SDI). Methods: We calculated the estimated annual percentage changes (EAPCs) to assess temporal trends in the age-standardized incidence rate, age-standardized mortality rate, and age-standardized DALYs of COPD from 1990 to 2019. Results: From 1990 to 2019, the COPD incidence and COPD-associated deaths and DALYs increased worldwide by 86%, 30%, and 26%, respectively. From 1990 to 2019, the global age-standardized incidence rate [EAPC, -0.11; 95% confidence interval (CI), -0.25 to 0.04], age-standardized mortality rate [EAPC, -2.10; 95% CI, -2.19 to -2.00], and age-standardized DALYs [EAPC, -1.87; 95% CI, -1.94 to -1.81] of COPD decreased. The age-standardized incidence of COPD increased most in areas with high SDI (EAPC 0.56). The largest increases in the age-standardized incidence rate of COPD were recorded in High-income North America (EAPC, 1.41), Southern Latin America (EAPC, 0.29), and North Africa and the Middle East (EAPC, 0.09). The three countries that recorded the largest increases in COPD incidence from 1990 to 2019 were the United States of America (EAPC, 1.51), Saudi Arabia (EAPC, 1.17), and Oman (EAPC, 1.10). Conclusions: Despite the decreased burden of COPD globally from 1990 to 2019, the age-standardized incidence rate of COPD increased in areas with high SDI, High-income North America, Southern Latin America, North Africa, and the Middle East.